Antecedents and Consequences of FOMO in Tourism: an Empirical Literature Review - Kurniawan, Cahya Nova; Susilo, Eko Agus (FIA UB, 2024)
This research aims to systematically review the literature on the drivers and consequences of the fear of missing out (FOMO) phenomena in the tourism context. This study employed a systematic literature review following PRISMA reporting guidelines. The writers searched the online database Elsevier (Scopus) for scholarly publications published in English that can be accessed throughout the databases. This study does a systematic literature review using data from 56 articles. According to the findings, three elements of antecedents contribute to FOMO in the tourism context: electronic word of mouth, reference groups, and perceived loneliness. Then, three variables are the results of the FOMO: intention to seek information, intention to visit, and positive well-being. FOMO is a